Between inner space and outer space - Barrow, John D. (Oxford University Press, 1999)
Now, in Between Inner Space and Outer Space, Barrow brings together dozens of essays that offer a sweeping account of his explorations along the boundary lines of science, philosophy, and religion. Here is an invigorating tour of topics such as cosmology, evolution, Grand Unified Theories, complexity and chaos, the nature of time, super string theory, quantum mechanics, particle physics, Big Bang theory, and much more. Barrow's range is remarkable. He examines, for instance, what science can tell us about our love of music or why certain paintings appeal to us. He recounts the dramatic discoveries made by the satellite COBE (Cosmic Background Explorer) and reveals what these findings tell us about the origins of the Cosmos. He discusses the debate over the nature of the universe waged by Stephen Hawking and Roger Penrose. And he offers a thoughtful review of E.O. Wilson's Consilience, seconding Wilson's criticism of social scientists who remain quite ignorant of the key insights made by the life sciences